Plankton community metabolism in Western Australia: estuarine, coastal and oceanic surface waters - Lara S García-Corral; Carlos Manuel Duarte; Susana Agustí (PANGAEA, 2021)
Here we present a total of 86 stations sampled in six different areas along the Western Australian Coast in the southeastern Indian Ocean. This dataset includes measurements of planktonic net community production (NCP), gross primary production (GPP) and community respiration (CR) off coastal, estuarine and open ocean surface (0.5–3 m) waters between 15 - 36 South and 107 - 122 East. We also reported the following data for each station: temperature (C), salinity, nitrate (μM), phosphate (μM), chlorophyll-a (mg/m^3), heterotrophic prokaryote abundance (cells/ml), Synechococcus abundance (cells/ml), picoeukaryotes abundance (cells/ml) and Prochlorococcus abundance (cells/ml).